Effect of N2/O2composition on inactivation efficiency of Escherichia coli by discharge plasma at the gas-solution interface - Zhigang Ke (2018)
© 2017 Elsevier GmbH Bacterial inactivation by discharge plasma is affected by many factors including gas type. No uniform conclusion for the effect of working gas type on the inactivation efficiency has been reached until now. In this work, the gas type and composition (O2, N2and air) on the inactivation efficiency of Escherichia coli by corona discharge plasma at the gas-solution interface produced using needle high-voltage electrode above the liquid were systemically investigated. It was found that air plasma had strong sterilization capability, followed by N2plasma, while O2plasma had the lowest sterilization capability. The reason for the gas type and composition to influence the sterilization capability was due to that they influenced the nitrite production in solution which further reacted with plasma-produced H2O2in acidified medium to form a strong oxidant peroxynitrite. The produced peroxynitrite could damage both the membrane and DNA, especially the former, and consequently inactivate the bacteria lethally.